1983
DOI: 10.1002/aja.1001670106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cartilage from young adult sea lamprey, Petromyzon marinus L: A new type of vertebrate cartilage

Abstract: Ultrastructural observations of cartilage from adult sea lamprey, Petromyzon marinus, reveal a highly cellular cartilage with an unusual extracellular matrix. The avascular cartilage is surrounded by a vascular perichondrium, which consists of dense connective tissue containing fibroblasts, collagen fibrils, and microfibrils. The cells (chondrocytes) vary in morphology in different parts of the cartilage in a way that may reflect their state of activity. Chondrocytes within the peripheral cartilage contain tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…It was demonstrated that fibrillar collagen is included as a minor component and that the SoxD and SoxE genes are coexpressed in the chondrocytes (Zhang and Cohn, 2006; Zhang et al, 2006a,b; Ohtani et al, 2008; Ota and Kuratani, 2010). However, on the other hand, the agnathan cartilage is mainly composed of elastin‐like fibers, including lamprin and myxnine (Wright and Youson, '83; Wright et al, '84; Robson et al, '93, '97). Thus, the matrix composition of the agnathan cartilage is unique in the vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that fibrillar collagen is included as a minor component and that the SoxD and SoxE genes are coexpressed in the chondrocytes (Zhang and Cohn, 2006; Zhang et al, 2006a,b; Ohtani et al, 2008; Ota and Kuratani, 2010). However, on the other hand, the agnathan cartilage is mainly composed of elastin‐like fibers, including lamprin and myxnine (Wright and Youson, '83; Wright et al, '84; Robson et al, '93, '97). Thus, the matrix composition of the agnathan cartilage is unique in the vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage based on type II collagen has long been considered a unifying character of gnathostomes that separates them from lampreys and hagfishes (1,19). Recently, we reported that lampreys possess two Col2␣1 orthologs and that adult lamprey cartilage is composed of Col2␣1 protein (2).…”
Section: Discussionmentioning
confidence: 99%
“…At least part of the neurocranium, and some of the branchial arches, but apparently not the mucocartilage, show contributions from the neural crest during embryogenesis (Langille and Hall 1988;Martin et al 2009). Instead, the ECM is composed of a network of 15-40 nm diameter, randomly arranged, branched fibrils (Wright and Youson 1983). 4.11).…”
Section: Cranial Skeletonmentioning
confidence: 99%
“…4.11). Verhoeff's stain implies an elastic nature to the lamprey ECM but the amino acid composition varies from elastin protein, leading to the name of lamprin for the major ECM protein of lamprey cartilage (Wright and Youson 1983). Fine structural studies show that the fibrous component of the extracellular matrix (ECM) of annular, piston, cranial, and dorsal plate cartilages is not collagen.…”
Section: Cranial Skeletonmentioning
confidence: 99%